Guanidinium‐Decorated Nanostructure for Precision Sonodynamic‐Catalytic Therapy of MRSA‐Infected Osteomyelitis. Issue 50 (4th November 2022) - Cheng, Yijie; Zhang, Yufei; Zhao, Zhe; Li, Gang; Li, Jie; Li, Anran; Xue, Yun; Zhu, Baolin; Wu, Zhongming; Zhang, Xinge
Abstract: Osteomyelitis caused by methicillin‐resistant Staphylococcus aureus (MRSA) biofilm infection is difficult to eradicate and can even be life‐threatening. Given that the infection is persistent and deep‐seated in the bone tissue, controlled and efficient treatment of osteomyelitis remains challenging. Herein, an activatable nanostructure (Au/TNT@PG) is presented for synergistic sonodynamic‐catalytic therapy of MRSA‐infected osteomyelitis. The Au/TNT@PG backbone is obtained by conjugating a guanidinium‐rich polymer (PG), a component that penetrates the biofilm matrix, onto ultrasound (US)‐absorbing gold‐doped titanate nanotubes (Au/TNTs). Under deep‐penetrating US irradiation, the nanocomposite generates 1 O2 for sonodynamic therapy and catalyzes the decomposition of endogenous H2 O2 into toxic OH in the acidic infection microenvironment for catalytic therapy, leading to bacterial cell death. Its robust antibacterial effectiveness is attributable to its bacteria‐capturing ability, the biofilm penetrability of positively charged guanidinium, and the subsequent synergistic effect of sonodynamic‐catalytic action of Au/TNT. Such a remotely controlled approach potentiates the polarization of macrophages to M2‐type while suppressing the M1‐type, leading to topical inflammation resolution and enhanced osteoblast proliferation and differentiation to inhibit bone loss. Therefore, this study provides a generic nanotherapeutic approach for efficient sonodynamic‐catalytic therapy with respect to osteomyelitis. Abstract : An activatable nanostructure is developed and assessed for outstanding biofilm disruption effect by capturing bacteria and penetrating biofilm matrix of guanidinium, and the synergistic sonodynamic‐catalytic effect. The remotely controlled nanostructure efficiently clears infection and mediates the inflammation resolution in methicillin‐resistant Staphylococcus aureus ‐infected osteomyelitis, thus providing a novel sonodynamic‐catalytic therapy for osteomyelitis.